Disease-mediated ecosystem services: Pathogens, plants, and people. (August 2020) - Paseka, Rachel E.; White, Lauren A.; Van de Waal, Dedmer B.; Strauss, Alex T.; González, Angélica L.; Everett, Rebecca A.; Peace, Angela; Seabloom, Eric W.; Frenken, Thijs; Borer, Elizabeth T.
Abstract : Despite the ubiquity of pathogens in ecological systems, their roles in influencing ecosystem services are often overlooked. Pathogens that infect primary producers (i.e., plants, algae, cyanobacteria) can have particularly strong effects because autotrophs are responsible for a wide range of provisioning, regulating, and cultural services. We review the roles of pathogens in mediating ecosystem services provided by autotrophs and outline scenarios in which infection may lead to unexpected outcomes in response to global change. Our synthesis highlights a deficit of information on this topic, and we outline a vision for future research that includes integrative theory and cross-system empirical studies. Ultimately, knowledge about the mediating roles of pathogens on ecosystem services should inform environmental policy and practice. Highlights: Pathogens are ubiquitous in nature, and they can play crucial roles in ecosystem processes. Pathogens mediate many ecosystem services on which humans rely. Pathogens that infect autotrophs (e.g., plants, algae, and cyanobacteria) may be especially important to human well-being because these hosts are fundamental to ecosystem function. While infectious disease is inherently negative from the perspective of infected hosts, pathogens infecting autotrophs can have positive or negative effects on ecosystem services. Global change induces shifts in pathogen prevalence and disease severity, which may lead to unexpected outcomes for ecosystem services. Understanding how pathogens impact ecosystem services can fundamentally improve our ability to make environmental decisions for a sustainable future.